Efecto de 14 semanas de entrenamiento de resistencia en el tejido muscular de ratas wistar - Castoldi, Robson Chacon; Teixeira, Giovana Rampazzo [UNESP]; de Malheiro, Olga Cristina Mello [UNESP]; Camargo, Regina Celi Trindade [UNESP]; Belangero, William Dias; Camargo Filho, José Carlos Silva [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2015)
The objective of the present study was to analyze the effects of 14 weeks of resistance training on muscle tissue in Wistar rats. 20 male Wistar rats were used in the study; 10 allocated to the untrained group (Group 1) and 10 to the trained (Group 2). The physical training (PT) program consisted of four sets of ten water jumps, three times a week for 14 weeks. A progressive increase in load was applied from the14nd to the 42nd day. Following this, the animals were euthanized with an overdose of potassium chlorate (100 mg/ kg) applied intraperitoneally. The ventral portion of the gastrocnemius muscle was removed for histological processing. The muscles were frozen in liquid nitrogen and cut into thicknesses of 5 µm using a rotative microtome. The sections were stained with hematoxylineosin for general analysis of the structure of muscles and analysis of the area of muscle fibers. The reaction with NADH-TR was utilized for differentiation between fast twitch (FT) and slow twitch (ST) fibers. The sections subjected to staining and histochemical reactions were observed in normal and polarized light and photomicrographed using a microscope (Zeiss®). The measurement of muscle fibers was performed using AxioVision software (Zeiss®). Statistical analysis was performed using the Student t test for analysis of the samples average. An average area of 5061.29 µm2 for Group 1 versus 5768.93 µm2 for Group 2 was observed. It can be concluded that 14 weeks of training with water jumps was effective in increasing muscle area. An increase in transverse area section (TAS) of ST and FT was also verified in the trained group.
Effects of 14 weeks resistance training on muscle tissue in wistar rats
Keywords: Physical Exercise; Striated muscle; Swimming